Study on the Recommended Placement and Air Distribution of Split Floor-Standing Room Air Conditioners - Zhang, Zhiheng; Gao, Yibu; Nie, Song; Tian, Yan; Li, Chenxi; Gao, Ran; Yin, Kui; Liu, Yu; Liu, Bo; Li, Hongbin (International Journal of Architectural Engineering Technology, 2022)
In recent years, split floor-standing room air conditioners have been widely used in civil and office buildings because of their high cooling capacity and easy installation, and the air draft sensation has attracted more and more attention. In this study, a target air supply evaluation index for regional thermal comfort evaluation in the work area, the air velocity target value, is proposed. A computational fluid dynamics model for common office is established, and a total of 204 working conditions are numerically simulated for each combination of different positions, different rotation angles, and different air supply velocities (1 m/s, 2 m/s and 3 m/s) of air conditioners in the room. The influence of the rotation angle of the air conditioner on the indoor air distribution was studied, and the distribution of the indoor velocity flow field at different positions was analyzed. The air-conditioning rotation angle that makes the velocity target value of the five preset planes in the room smaller under different conditions is summarized as the recommended rotation angle. The numerical simulation results were verified by experimental means and found to be consistent with the measured results. This study can provide theoretical guidance and reference for the placement of indoor air conditioning units for users in real life.